2005
DOI: 10.1002/marc.200400445
|View full text |Cite
|
Sign up to set email alerts
|

A Low Curing Temperature Silver Ink for Use in Ink‐Jet Printing and Subsequent Production of Conductive Tracks

Abstract: Summary: A drop‐on‐demand ink‐jet printer has been used to print a silver‐organic solution onto glass substrates. Conductive silver tracks were obtained by heat treatment of the ink‐jet printed deposits at temperatures ranging from 125 °C–200 °C in air. Resistivity values were found to have dropped to two to three times the theoretical resisitivity of bulk silver after temperatures of 150 °C and above were used.Resistivity values of a silver‐based ink.magnified imageResistivity values of a silver‐based ink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
206
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(212 citation statements)
references
References 11 publications
2
206
1
3
Order By: Relevance
“…Dearden et al [193] reported inkjet printing of solutions of Ag neodecanoate. Preparation of the ink involved the straightforward synthesis of the Ag salt followed by its dissolution in xylene.…”
Section: Silver Inksmentioning
confidence: 99%
“…Dearden et al [193] reported inkjet printing of solutions of Ag neodecanoate. Preparation of the ink involved the straightforward synthesis of the Ag salt followed by its dissolution in xylene.…”
Section: Silver Inksmentioning
confidence: 99%
“…Many polymer thin films, containing noble metal nanoparticles, have been prepared by reducing polymer metal chelate films such as polyaniline/Au, poly(vinyl alcohol)/ Ag, poly(acrylic acid)/Cu. [14][15][16] The use of silver organic complexes has also been reported as a new method of obtaining silver nanoparticles and conductive silver tracks and coatings, where silver carboxylate 17 and silver alkylcarbamate complexes 18,19 are reduced to silver metal simply by heating.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments using more concentrated metal colloids are underway with the objective of electrohydrodynamic deposition of even finer conductive tracks. (29) colloid solution 3nm -5μm Laser direct write (30) Gold Ink --8μm Ink-jet Printing (7) Gold nanoparticles in toluene 2-5nm 30 15μm Ink-jet Printing (31) Gold nanoparticles in toluene 2-4nm 30 20μm Ink-jet Printing (32) Gold nanoparticles in toluene 5-20nm 30-50 100μm Ink-jet Printing (33) Gold nanoparticles in toluene 2-4nm 30 125μm Ink-jet Printing (34) Silver nanoparticles in ␣-terpineol 5-7nm 10 100μm Ink-jet Printing (35) Silver nanoparticles in toluene 1-10nm 30 120μm Ink-jet Printing (36) Silver ink in xylene -16 160μm Ink-jet Printing (37) Silver nanodispersion 50nm 8 1.5mm Microcontact Printing (38) Copper --500nm Chemical Vapor Deposition (39) Copper --1μm…”
Section: Resultsmentioning
confidence: 99%